A Fatal Case of Nafcillin-Induced Hepatotoxicity: A Case Report and the Literature Review - Mian Bilal Alam; Amin Kadoura; Magesh Sathaiah (Case Reports in Medicine)
Background. Drug-induced hepatotoxicity (DIH) is quite common, and there are several recommendations for its treatment based upon its etiology. DIH may range from mild and subclinical to fulminant liver failure and death. Even though there is extensive list of drugs causing DIH, antibiotics, as a class of drugs, are the most common cause of DIH. Here, we present a fatal case of nafcillin-induced hepatotoxicity confirmed by liver biopsy, with total bilirubin peaking to 21.8 mg/dl and subsequent further extensive evaluation for hepatic injury turning out to be negative.